2022
DOI: 10.12659/msm.935307
|View full text |Cite
|
Sign up to set email alerts
|

Combining Magnetic Resonance Diffusion-Weighted Imaging with Prostate-Specific Antigen to Differentiate Between Malignant and Benign Prostate Lesions

Abstract: Background We aimed to develop a combined model of quantitative parameters derived from 3 different magnetic resonance imaging (MRI) diffusion models and laboratory data related to prostate-specific antigen (PSA) for differentiating between prostate cancer (PCa) and benign lesions. Material/Methods Eighty-four patients pathologically confirmed as having PCa or benign disease were enrolled. All patients underwent multiparametric MRI before biopsy, added intravoxel incohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…PSA is considered as the commonly clinical indicator in the examination of prostate malignant tumor. PSA was also usually performed as a marker in the screening and assessment of treatment effect in prostate malignant tumor [ 6 ]. Previous research studies found that increased PSA levels were closely associated with the clinical phase of prostate malignant tumor and the higher PSA concentration indicated the worse damage of surrounding tissues and malignant degree [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSA is considered as the commonly clinical indicator in the examination of prostate malignant tumor. PSA was also usually performed as a marker in the screening and assessment of treatment effect in prostate malignant tumor [ 6 ]. Previous research studies found that increased PSA levels were closely associated with the clinical phase of prostate malignant tumor and the higher PSA concentration indicated the worse damage of surrounding tissues and malignant degree [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, using MRI alone has some limitations. It was reported that could MRI only find morphological information and was not able to obtain the internal microstructure of tumor tissues, resulting in difficult evaluation for the risk of prostate tumors [ 6 ]. Another study showed that diffusion-weighted MRI could well manifest the tissue of tumor with abundant vascularity; however, the diagnostic role for prostate malignant tumor was debated [ 7 ].…”
Section: Introductionmentioning
confidence: 99%